Rural perception of the premontane wet forest conservation (P-wf) - Sancho-Jiménez, Luis Felipe (2023)
The rural perception of forest conservation was determined in La Paz, Piedades Norte, San Ramón, Alajuela, Costa Rica. This rural community is located in the buffer zone of the Alberto Manuel Brenes Biological Reserve (ReBAMB), its economy is based on agriculture, livestock and nature tourism. In La Paz, a housing census was applied; in addition, three workshops with focus groups were held. For data analysis, the IBM SPSS Statistics Base 22.0 program was used. 194 interviews were completed. 46.4% of the census population were men and 53.6% women. The age composition was ≥ 15 ≤ 89 years, with a mode of 53 years. 79.4% of the people interviewed have lived their entire lives in La Paz. 84% of the population perceive benefits associated with forest conservation and they mention water as the main resource. 94% of the people consider it necessary to have conservation laws. 92% of interviewed people expect their family to stay and live in the same community. On the other hand, 49.5% of the population perceives that there are threats to forest conservation (316 mentions), with the greatest risk associated with deforestation (26.8%), pollution (23.19%), urban expansion (20.61%) and use of agrochemicals (19.07%). 97.42% of the people registered mentioned that they like to live in peace and relate it to the beauty of the landscape, tranquility and a good quality of life.